An unusual case of intraosseous vascular malformation of the maxilla mimicking fibrous dysplasia: a case report and literature review on imaging features of intraosseous vascular anomalies of the jaw - Kim, J-E (The British Institute of Radiology., 2014)
Intraosseous vascular malformation (IVM) is a relatively rare pathological condition that may pose significant risks, such as excessive bleeding, during surgical procedures. We present a case of an 18-year-old female patient with firm swelling in the left maxilla. A bony expansion over the left half of the maxilla with preservation of the outer cortex and a ground glass appearance on CT images initially revealed a possibility of fibrous dysplasia. However, a tentative diagnosis of IVM was made based on the vascular nature of the lesion as well as the patient's surgical history and additional imaging findings. IVM should be included in the differential diagnosis of an expansile bony lesion with trabecular alteration. Through the literature review, it was found that imaging findings, such as a neurovascular canal widening on CT images and a hyperintense signal on T(1) weighted MR images, might be helpful in differentiating IVM from other pathologies.